Student-Teachers as Editors and Writers: a Pedagogical Design to Examine Peer Edition Through Formative Assessment - Sanabria Mariño, Miguel Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The present pedagogical proposal describes an initial implementation of a peer-editionprocess as a formative assessment strategy conducted with a group of nine firstsemesterTeacher Education Program students in a public school in Guadalupe Santander. On the whole, the study sought to identify and characterize how peer-editing could enhance students’ writing abilities. Thepedagogical design aimed at developing students’ awareness in relation to their roleas student editors and student writers and promoting autonomy in the process of learners’ composition exercise to encourage collaboration and cognitive development in the composition process evolution. Thepiloting of a peer-editing cycle based on process writing and peer-editing principles was proposed, implemented and finally evaluated. Insights from the process were gathered and considered to refine and polish forthcoming cycles.